2015
DOI: 10.1097/tp.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytokine, Chemokine and Growth Factor Expression in Phenotypes of Chronic Lung Allograft Dysfunction

Abstract: There were major differences in cytokine and chemokine expression in our different study groups. Especially IL-6, but also IP-10/CXCL10, and VEGF may be interesting mediators in RAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 21 publications
(21 reference statements)
5
49
1
Order By: Relevance
“…The presence of HLA antibodies seems to be more associated with rCLAD compared to BOS which is in line with the hypothesis of (at least part) overlap (65). Of interest is also that in BAL, VEGF levels are decreased in rCLAD patients (34), which is in line with the hypothesis that the capillary network is of importance, which was also demonstrated in a descriptive pathological study (66). In contrast, the lymphatics do not seem to be altered in rCLAD, which is surprising given the predominant distribution (pleural and septal) of fibrosis in rCLAD (67).…”
Section: Risk Factors and Mechanismssupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of HLA antibodies seems to be more associated with rCLAD compared to BOS which is in line with the hypothesis of (at least part) overlap (65). Of interest is also that in BAL, VEGF levels are decreased in rCLAD patients (34), which is in line with the hypothesis that the capillary network is of importance, which was also demonstrated in a descriptive pathological study (66). In contrast, the lymphatics do not seem to be altered in rCLAD, which is surprising given the predominant distribution (pleural and septal) of fibrosis in rCLAD (67).…”
Section: Risk Factors and Mechanismssupporting
confidence: 71%
“…In fact, a recent BAL cytokine and chemokine analysis, could not detect any molecule that was differentially regulated between stable (non-rejecting) patients and patients with BOS (34). Consequently, some groups have tried to identify blood markers blood for BOS development, but so far none have proven to be very sensitive and specific.…”
Section: Risk Factors and Mechanisms Of Bosmentioning
confidence: 99%
“…It was also found that after liver transplantation in patients with recurrent hepatitis plasma CXCL-10 could differentiate patients with slow from those with rapid progression of fibrosis 50 . Moreover, in a biomarker discovery study in lung transplant patients, CXCL-8, CXCL-10, CCL-2, CCL-3, CCL-4 CCL-7, and CCL-3 in bronchial lavage fluid could differentiate between different phenotypes of chronic lung allograft dysfuntion 51 . A few clinical targeted proteomics/protein biomarker studies in heart transplant patients have also been described (for a review, please see reference 9 ).…”
Section: Predictive Biomarkers In Transplantation Based On Targeted Pmentioning
confidence: 99%
“…Compared with the much better known BOS clinical phenotype, patients with RAS experience a worse prognosis (3.5 versus 1.5 years); the reasons for this difference in prognosis are poorly understood [7]. Patients affected by RAS appear to progress in a more stepwise pattern [8], that might be driven by intermittent up-regulation of pro-inflammatory mediators [9,10] during episodes of diffuse alveolar damage [11,12] similar to those observed in patients with idiopathic pulmonary fibrosis (IPF).…”
Section: Introductionmentioning
confidence: 99%